Epitaxy of Single‐Crystalline GaN Film on CMOS‐Compatible Si(100) Substrate Buffered by Graphene. (23rd July 2019) - Feng, Yuxia; Yang, Xuelin; Zhang, Zhihong; Kang, Duan; Zhang, Jie; Liu, Kaihui; Li, Xinzheng; Shen, Jianfei; Liu, Fang; Wang, Tao; Ji, Panfeng; Xu, Fujun; et al.
Abstract: Fabricating single‐crystalline gallium nitride (GaN)‐based devices on a Si(100) substrate, which is compatible with the mainstream complementary metal‐oxide‐semiconductor circuits, is a prerequisite for next‐generation high‐performance electronics and optoelectronics. However, the direct epitaxy of single‐crystalline GaN on a Si(100) substrate remains challenging due to the asymmetric surface domains of Si(100), which can lead to polycrystalline GaN with a two‐domain structure. Here, by utilizing single‐crystalline graphene as a buffer layer, the epitaxy of a single‐crystalline GaN film on a Si(100) substrate is demonstrated. The in situ treatment of graphene with NH3 can generate sp 3 CN bonds, which then triggers the nucleation of nitrides. The one‐atom‐thick single‐crystalline graphene provides an in‐plane driving force to align all GaN domains to form a single crystal. The nucleation mechanisms and domain evolutions are further clarified by surface science exploration and first‐principle calculations. This work lays the foundation for the integration of GaN‐based devices into Si‐based integrated circuits and also broadens the choice for the epitaxy of nitrides on unconventional amorphous or flexible substrates. Abstract : A single‐crystalline gallium nitride (GaN) film with atomic‐step terraces is realized on a complementary metal‐oxide‐semiconductor‐compatible Si(100) substrate by using a one‐atom‐thick single‐crystalline graphene buffer layer. The monolayer single‐crystalline graphene provides an in‐plane driving force for the uniform alignment of nitrides domains. This approach can also enable the growth of wafer‐scale hexagonal single‐crystalline films on amorphous or flexible substrates.